On the way to the beach - Cole, Henry, 1955- (Greenwillow Books, 2003)
A walk through the woods into a salt marsh over the dunes and onto the beach brings encounters with a variety of animals and plants whose identity is revealed by folding out flaps that appear on alternate pages.